2011
DOI: 10.1530/eje-11-0512
|View full text |Cite
|
Sign up to set email alerts
|

Altered urinary excretion of aquaporin 2 in IgA nephropathy

Abstract: Objective: The intrarenal renin-angiotensin system (RAS) activation plays a pivotal role in immunoglobulin A nephropathy (IgAN) pathogenesis, which is still largely undefined. Recently, vasopressin (AVP) has been advocated to contribute to the genesis and progression of chronic kidney diseases (CKD) directly, and indirectly, via RAS activation. Our aim is to explore the intrarenal activity of AVP, its relationship with RAS activity, as well as its modulation by therapies in IgAN. Design: In this observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…All the spectra were normalized by means of total ion current. The reproducibility of the SELDI analysis, assessed as previously described [20], was comparable to that in our previous works [22, 23]. Only mass peaks showing a statistically significant different expression (p<0.05) between cases and controls were considered for further analyses.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…All the spectra were normalized by means of total ion current. The reproducibility of the SELDI analysis, assessed as previously described [20], was comparable to that in our previous works [22, 23]. Only mass peaks showing a statistically significant different expression (p<0.05) between cases and controls were considered for further analyses.…”
Section: Methodsmentioning
confidence: 58%
“…Urinary proteomics by the so-called profiling technologies may overcome some of the limitations of laborious gel-based approaches, thus resulting more appropriate for clinical proteomics studies [21]. Recent reports demonstrated that urinary peptides and proteins could serve as specific biomarkers for chronic kidney diseases (CKD) [2223] and uro-genital cancers [24]. However, most of the studies carried out so far have primarily compared patients to healthy controls, making it difficult to ascertain the specificity and sensitivity of the potential biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…6 The results of our study contradict the data of Rocchetti et al, who reported a rise in the renal excretion of AQP2 in untreated patients with immunoglobulin A (IgA) nephropathy. 11 Furthermore, patients with a greater deterioration of kidney function, higher proteinuria, and arterial hypertension displayed even higher urinary AQP2 excretion; moreover, a decrease of daily proteinuria following treatment was asso-ciated with a fall of the urinary AQP2 level. The authors suggested that an increase in the urinary excretion of AQP2 may reflect enhanced intrarenal AVP and renin-angiotensin system (RAS) activity, as well as the severity of renal damage.…”
Section: Discussionmentioning
confidence: 98%
“…For these reasons, different proteomics approaches have been carried out for biomarker discovery, which might be an important step forward to the noninvasive diagnosis of kidney diseases, including IgAN [83,87,88]. Among Using proteomic approaches, several potential urinary biomarkers have been identified for the diagnostic and prognostic evaluation of IgAN, including aquaporin 2 [89], laminin G-like 3 [90,91], free kappa light chains [90] and other peptides such as bradykinin, uromodulin and alpha-1-antitrypsin [88]. Other proteins have been suggested as potential prognostic biomarkers in IgAN including afamin, leucine-rich alpha-2-glycoprotein, ceruloplasmin, alpha-1-microgolbulin, hemopexin, apolipoprotein A-I, complement C3, vitamin D-binding protein, beta-2-microglobulin and retinolbinding protein 4.…”
Section: Proteomics and Micrornasmentioning
confidence: 99%